2020
DOI: 10.3390/nano10061215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Adsorption of NH3 and NO2 on Zr and Hf Dichalcogenides (S, Se, Te) Monolayers: A Density Functional Theory Study

Abstract: Due to their atomic thicknesses and semiconducting properties, two-dimensional transition metal dichalcogenides (TMDCs) are gaining increasing research interest. Among them, Hf- and Zr-based TMDCs demonstrate the unique advantage that their oxides (HfO2 and ZrO2) are excellent dielectric materials. One possible method to precisely tune the material properties of two-dimensional atomically thin nanomaterials is to adsorb molecules on their surfaces as non-bonded dopants. In the present work, the molecular adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…NH 3 is a donor to the Zn 2 TaN 3 monolayer, as for most of 2D materials, but it is hardly removable (t = 1.56 Â 10 7 s) from its surface, which is different from most of 2D materials, where NH 3 possesses a weak van der Waals interaction. [96][97][98][99] NO and NO 2 induce local dipoles of a different orientation on the Zn 2 TaN 3 monolayer surface, which can facilitate their detection. 100,101…”
Section: Resultsmentioning
confidence: 99%
“…NH 3 is a donor to the Zn 2 TaN 3 monolayer, as for most of 2D materials, but it is hardly removable (t = 1.56 Â 10 7 s) from its surface, which is different from most of 2D materials, where NH 3 possesses a weak van der Waals interaction. [96][97][98][99] NO and NO 2 induce local dipoles of a different orientation on the Zn 2 TaN 3 monolayer surface, which can facilitate their detection. 100,101…”
Section: Resultsmentioning
confidence: 99%
“…Transition-metal dihalogenate (TMD) layered materials have not only excellent physical and chemical properties but also band gaps that graphene lacks, which has led to their increased use in gas sensors. For example, Liu et al used density functional theory (DFT) to investigate the gas-sensitive properties of Ir-modified MoS 2 monolayer films to three typical gases in transformer oil: methane (CH 4 ), ethane (C 2 H 4 ), and acetylene (C 2 H 2 ). Based on the analysis of state density (DOS) and charge density difference (CDD), it is shown that Ir decorated MoS 2 has a great prospect as a gas sensor for dissolved gas detection .…”
Section: Introductionmentioning
confidence: 99%
“…For example, due to its high conductivity, intrinsic kinematics, robustness, mixed valence state, and efficient and durable electrochemical activity, Co 9 S 8 is considered a promising electrocatalyst material [13][14][15], but it suffers from poor electrochemical activity arising from its sluggish kinetics during catalytic OER and HER processes [18][19][20]. The catalytic activity of an electrocatalyst is mainly determined by its electronic structure, which can be altered intrinsically via the addition of heteroatoms (e.g., N and S) to the host structure [21,22]. The unfilled outermost 2p and 3p respective orbitals of N and S exhibit promising electron-withdrawing ability and high electronegativity due to the capture of electrons from adjacent Co atoms via acceptor/donor interactions [17,21,23].…”
Section: Introductionmentioning
confidence: 99%